Variasi Leksikal Bahasa Sasak di Kecamatan Karangasem: Kajian Dialektologi - ., Zulkarnaen; Dhanawaty, Ni Made; Putu Putra, Anak Agung (Humanis, 2021)
This article discusses the lexical variations of the Sasak language in Karangasem. The reason for choosing this object, is to explain the various dialects used by the community in the villages of Tumbu, Tegal Linggah, and Bukit, Karangasem. The problem is focused on two things, namely the lexical variation of the Sasak language in Karangasem and the grouping of Sasak lek languages ??in Karangasem using dialectometry theory and the isogloss file from Zulaeha. The method used, namely the proficient methods with fishing techniques, note taking techniques, and record techniques. Analysis of the lexical variations in the Sasak Karangasem language shows that there are various kinds of lexical variations in each TP based on old adulthood. Lexical variations of the fields meaning time, season, natural state, natural objects, and directions, three are found in the 'cloud' glossary. Kinship system, two berian are found in the 'wife' glossary. In animals and their parts, three berries are found in the 'worm' glossary. Movement and work, three berries are found in the 'walking' glossary. Limbs and parts there are found two beros in 'blood' gloss. Properties, numbers, and sizes, we find two entries in the 'good' glossary. In plants, fruits and colors, two berian are found on the 'tree' glossary. Question words, conjunctions, and objects found one berian in ‘how’ glossos. Pronouns and days found four words in the glossary "you".